The Story Of Prophet Ayyub - "Khan, Saniyasnain" (China; goodwordbooks, 2024)
The Story of Prophet Ayyub (AS) is a delightful board book that makes a perfect gift for little children. It introduces young readers to the inspiring Quranic story of Prophet Ayyub, known for his unwavering patience and deep trust in Allah during times of hardship. Told in simple, engaging language and accompanied by charming illustrations, the story gently teaches children about resilience, gratitude, and faith. As they follow the trials faced by Prophet Ayyub and how he turned to Allah with patience and prayer, children are encouraged to reflect on the importance of staying hopeful and thankful, even in difficult times. The book concludes with a clear moral, helping children understand the powerful lesson behind the story. Designed for little hands and big hearts, this board book is an excellent addition to any child's Islamic book collection
Keywords: Prophets Story